Health Performance Evaluation of Rural Drinking Water Safety Project Based on Time-varying DID Method - GUO Xiaohong; LI Changyan (Renmin Zhujiang)
As an important project of poverty alleviation,the “Rural Drinking Water Safety Project” is a key livelihood policy to solve the drinking water shortage for rural residents.Based on the panel data of 450 villages and communities from 150 counties in China in 2011,2013,2015,and 2018,the time-varying difference-in-difference method is used to evaluate the impacts of the Rural Drinking Water Safety Project on residents' health conditions.In addition,a further robustness test is conducted combined with matching and the difference-in-difference method.The conclusions of the empirical analysis are as follows.①Rural Drinking Water Safety Project can significantly improve the overall health and physical functions of rural residents and relieve their mental depression and physical pain.②Further heterogeneous analysis finds that the Project has a higher effect on the health improvement of female residents than that of male residents,and especially it can significantly relieve women's physical pain.③The Project has a significant effect on the improvement of residents from good family economic conditions but cannot greatly improve residents from poor families.This paper can provide policy reference for the further improvement of the Rural Drinking Water Safety Project.